(untitled) (Journal of the College of Education for Women, 2019)
“Child of today is a man of the future" this slogan is one of the most popular logos of international organizations and institutions that dealing with human beings needs in general and children needs in particular, whether these needs are educational, health, social, or economic. Children require special care and extra legal protection, since the child-raising is not the Child’s own issue, but it’s the issue of the society in which he/she would integrate. As the education and language skillsacquisition primarily associated with hearing, because human being receives most of the skills and knowledge through the hearing; that imitate sounds and learn how to speak isacquired only by hearing, so therefore the hearing - impairedchild could not speak due to his/her inability to hear sounds. humans depend on what they hear and react to voices accordingly, by this react they would acquire skills and information that attain them the communicate with those around.This study aims to determine the effectiveness of an early intervention of program basing on illustrative pictures to teach a group of children withhearing impairment some concepts, the children’s age range is from (4-6) years, and after homogenizing between the sample’s individuals the researchers used the “Early Intervention Program” (prepared by the researchers). In this study the quasi-experimentalapproach has been used on the sample using the pre and post measurements, where the learning program considered as the independent variable and the other concepts as the dependent variables.